"Let's Get Ready to Crumble": Black Municipal Leadership and Public Housing Transformation in the United States. Issue 2 (March 2021) - Owens, Michael Leo; Drake Rodriguez, Akira; Brown, Robert A.
U.S. cities transform public housing. Black municipal leadership (BML) may influence the scale and character of public housing removal and redevelopment. Informed by the "Black urban regime" literature, this study assesses whether presence and duration of BML, coupled with other factors, explains variation in public housing transformation for a sample of large cities. Its findings suggest that, controlling for other factors, BML is associated with moderately greater scales of public housing removal in the 1990s and 2000s, but BML is not associated with the "rate of return" by former public housing residents or new residence by public housing eligible households in Housing Opportunities for People Everywhere (HOPE VI) communities as of 2016. The findings invite further research on the intraracial dynamics and policy consequences of BML. They build, too, on public housing transformation scholarship, raising new questions about how municipal politics shape public housing and other sites of subsidized residence for low-income denizens of cities.